PELAKSANAAN PERATURAN MENTERI BUMN NOMOR:PER-01/MBU/2011 TENTANG PENERAPAN TATA KELOLA YANG BAIK (GOOD CORPORATE GOVERNANCE) PADA BUMN (Studi Kasus Di PT Perkebunan Nusantara IV) - Hartono, Rudi (Universitas Medan Area, 2016)
Good Corporate Governance can be understood as a set of regulations governing Limited Liability relationship between shareholders, management companies and other stakeholders with regard to the rights and obligations, one of which is the decision-making at the Board of Directors and Board of Commissioners. The provisions stipulated in the Regulation of the Minister of SOE No. PER-01 / MBU / 2011,the publication of these regulations ultimately aims to create corporate governance that provides added value for all parties. Barriers to implementation of Good Corporate Governance is composed of several factors, among others, legal, corporate culture and human resources, but the implementation of PT Perkebunan Nusantara IV remain committed. As part of its commitment to the forming section, which is responsible for monitoring and encouraging implementation of application in accordance with the provisions of the Law.